The devil we don't know the dark side of revolutions in the Middle East - Darwish, Nonie (John Wiley & Sons, 2012)
Nonie Darwish assesses the potential for freedom to succeed following the recent revolutions in the Middle East. The recent powerful wave of Middle East uprisings has fueled both hope and trepidation in the region and around the world as the ultimate fate-and fallout-of the Arab spring continue to hang in the balance. Born and raised as a Muslim in Egypt and now living in the United States, Nonie Darwish brings an informed perspective to this carefully considered assessment of the potential outcome of the revolutions in the Middle East. This thought-provoking book will add to the ongoing debate on what the future holds for the people and the politics of the region and on the ultimate compatibility of freedom and democracy in the Muslim world. Takes an unflinching, in-depth look at the ramifications of the game-changing recent uprisings in the Middle East Examines that factors that will obstruct or support freedom and democracy in the Muslim world.